The core normal Type Ia supernova 2019np – an overall spherical explosion with an aspherical surface layer and an aspherical 56Ni core. Issue 1 (16th January 2023) - Hoeflich, Peter; Yang, Yi; Baade, Dietrich; Cikota, Aleksandar; Maund, Justyn R; Mishra, Divya; Patat, Ferdinando; Patra, Kishore C; Wang, Lifan; Wheeler, J Craig; Filippenko, Alexei V; Gal-Yam, Avishay; et al.
ABSTRACT: Optical spectropolarimetry of the normal thermonuclear supernova (SN) 2019np from −14.5 to +14.5 d relative to B -band maximum detected an intrinsic continuum polarization ( p cont ) of 0.21 ± 0.09 per cent at the first epoch. Between days −11.5 and  +0.5, p cont remained ∼0 and by day +14.5 was again significant at 0.19 ± 0.10 per cent. Not considering the first epoch, the dominant axis of ${\rm Si\, {\small II}}$  λ6355 was roughly constant staying close the continuum until both rotated in opposite directions on day  +14.5. Detailed radiation-hydrodynamical simulations produce a very steep density slope in the outermost ejecta so that the low first-epoch p cont ≈ 0.2 per cent nevertheless suggests a separate structure with an axis ratio ∼2 in the outer carbon-rich (3.5–4) × 10 −3  M⊙ . Large-amplitude fluctuations in the polarization profiles and a flocculent appearance of the polar diagram for the ${\rm Ca\, {\small II}}$  near-infrared triplet (NIR3) may be related by a common origin. The temporal evolution of the polarization spectra agrees with an off-centre delayed detonation. The late-time increase in polarization and the possible change in position angle are also consistent with an aspherical 56 Ni core. The p cont and the absorptions due to ${\rm Si\, {\small II}}$ λ6355 and ${\rm Ca\, {\small II}}$  NIR3 form in the same region of the extended photosphere, with an interplay between line occultation and thermalization producing p . Small-scale polarization features may be due to small-scale structures, but many could be related to atomic patterns of the quasi-continuum; they hardly have an equivalent in the total-flux spectra. We compare SN 2019np to other SNe and develop future objectives and strategies for SN Ia spectropolarimetry.